Skeletal, Dental, and Soft Tissue Changes after Slow Maxillary Expansion in Early Mixed Dentition - Özgür Kocaali; Nurver Karslı (Turkish Journal of Orthodontics)
Objective: This study aimed to evaluate the skeletal, dental, and soft tissue effects of the nickel titanium memory Leaf Expander in a growing sample of patients with unilateral posterior crossbite compared with a control group using digital models and lateral cephalometric radiographs. Methods: The research included a total of 24 patients, 12 of whom were treated and 12 untreated. The Leaf Expander group consisted of 4 males and 8 females (mean age= 8.6±10.7 years), and the control group consisted of 5 males and 7 females (mean age: 9.2±0.8 years). Changes during the observation period in both groups were evaluated using the Wilcoxon signed-rank test. We used the Mann-Whitney U test to compare the data between the groups. Results: There was a significant increase in the values indicating the vertical position of the maxilla and mandible in the treatment group. The palatal surface area increased significantly in both groups, but the increase was significantly higher in the treatment group than in the control group. In addition, intermolar width and arch perimeter measurements were significantly higher in the treatment group than in the control group. Conclusion: With the advantage that this device does not require parent compliance, the possibility of incorrect activation was eliminated, and effective expansion using the Leaf Expander was achieved in patients with unilateral crossbite.